2018
DOI: 10.3892/mmr.2018.8951
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA TP73‑AS1 predicts poor prognosis and promotes cell proliferation in ovarian cancer via cell cycle and apoptosis regulation

Abstract: TP73‑AS1, a critical cancer‑associated long noncoding RNA (lncRNA), has been identified in esophageal cancer and glioma. However, its biological role in ovarian cancer (OC) remains to be investigated. The aim of the present study was to investigate the role of TP73‑AS1 in human OC cell lines and clinical tumor samples to determine the function of this molecule. Reverse transcription‑quantitative polymerase chain reaction analysis was carried out to detect that TP73‑AS1 was upregulated in OC tissues and cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…These findings indicate that the expression of lncRNA is tissue-specific and individualized, so they cannot be used as specific tumor markers for cervical cancer. The findings from the present study showed that the expression of lncRNA TP73-AS1 was significantly increased in cervical cancer tissues and cell lines when compared with normal tissues and NCEC cells, and promoted cell proliferation, which is consistent with previous studies on lncRNA TP73-AS1 in other cancers [10,12,13].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings indicate that the expression of lncRNA is tissue-specific and individualized, so they cannot be used as specific tumor markers for cervical cancer. The findings from the present study showed that the expression of lncRNA TP73-AS1 was significantly increased in cervical cancer tissues and cell lines when compared with normal tissues and NCEC cells, and promoted cell proliferation, which is consistent with previous studies on lncRNA TP73-AS1 in other cancers [10,12,13].…”
Section: Discussionsupporting
confidence: 92%
“…Long non-coding RNAs (lncRNAs) are transcripts of more than 200 nucleotides and have no protein-coding potential [9]. LncRNA P73 antisense RNA 1T (TP73-AS1), located on chromosome 1p36, has been identified in hepatocellular carcinoma [10], breast cancer [11], glioma [12], esophageal squamous cell carcinoma [9] and ovarian cancer [13], where it has been shown to promote cell proliferation and tumorigenesis [913]. However, the underlying mechanism of lncRNA TP73-AS1 in cervical cancer remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 For example, TP73-AS1 knockdown hampered ovarian cancer cell growth by modulating cell apoptosis, and also effectively elevated the survival time of patients with this disease. 18 MALAT1 stimulated epithelial ovarian cancer cell viability as well as cell migration and invasion. 19 Moreover, DUXAP10 was indicated as a potential therapeutic biomarker for ovarian cancer.…”
Section: Discussionmentioning
confidence: 96%
“…A total of 19 articles were eligible for this meta-analysis according to the selection criteria [9][10][11][12][13][16][17][18][19][20][21][22][23][24][25][26][27] . In total, 1329 patients with 13 types of cancer, including GC 9,[16][17][18] , breast cancer 13,19 , ovarian cancer 20,21 , osteosarcoma 12,22 , brain glioma 23 , hepatocellular carcinoma (HCC) 11 , cholangiocarcinoma (CCA) 13 , colorectal cancer (CRC) 27 , pancreatic cancer 24 , lung adenocarcinoma (LAD) 25 , non-small cell lung cancer (NSCLC) 19 , bladder cancer 10 and clear cell renal cell carcinoma (ccRCC) 26 , were analyzed. Twelve articles chose overall survival (OS) as the only survival outcome 9,11-13,17-19,21-25 , 2 articles used both OS and disease-free survival (DFS) 16,26 , and one article used both OS and progression-free survival (PFS) 10 .…”
Section: Discussionmentioning
confidence: 99%